2010
DOI: 10.1002/hep.23426
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of mitochondrial antiviral signaling protein in the liver of patients with chronic hepatitis C correlates with a reduced activation of the endogenous interferon system†

Abstract: Hepatitis C virus (HCV) infection induces the endogenous interferon (IFN) system in the liver in some but not all patients with chronic hepatitis C (CHC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 38 publications
6
87
0
Order By: Relevance
“…When endogenous IFN production is low (for example, owing to HCV-mediated cleavage of mitochondrial antiviral signaling protein (MAVS) 43,54 ) and IFN effector function potent, infection is established because of inadequate stimulation of the IFN network. ISG levels are predicted to be low in such individuals before treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When endogenous IFN production is low (for example, owing to HCV-mediated cleavage of mitochondrial antiviral signaling protein (MAVS) 43,54 ) and IFN effector function potent, infection is established because of inadequate stimulation of the IFN network. ISG levels are predicted to be low in such individuals before treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[28,29] All our HCV-4 patients had suboptimal vitamin D levels with the majority being severely deficient (86%). Possible explanations for the association of HCV with vitamin D deficiency have included decreased 25-alpha hydroxylation in the liver, HCV may have the ability to directly suppress 25-alpha hydroxylation through inducing cytokines and oxidative stresses, and a recent study has shown that HCV alters lipid metabolism directly reducing production of 7-dehydrocholesterol, the precursor of endogenouslyproduced vitamin D. [30,31] The independent effect of HCV on vitamin D levels is strongly supported by our finding of the remarkable improvement in vitamin D levels after successful eradication of HCV and its persistence in non-responders. Further studies are definitely recommended to depict the exact mechanisms by which HCV alters vitamin D production and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the observation that in HCV-infected Huh7 cells, MAVS is cleaved by the viral protease has been confirmed in humans (Bellecave et al, 2010). By using Western blot analyses of cell lysates prepared from liver biopsies a convincing correlation was found between the degree of MAVS cleavage and HCV infection.…”
Section: Innate Immune Responses In Hcv-infected Humansmentioning
confidence: 82%
“…By using Western blot analyses of cell lysates prepared from liver biopsies a convincing correlation was found between the degree of MAVS cleavage and HCV infection. Moreover, the amount of uncleaved MAVS was clearly reduced as compared with liver biopsies from patients with non-HCV liver diseases (Bellecave et al, 2010). Whether TRIF is also cleaved in vivo has not been determined thus far.…”
mentioning
confidence: 96%